Effectiveness of Project-Based Scratch Programming to Improve Problem-Solving Skills of Elementary School Students - Putra, Galih Mahardika Christian; Prasetyaningtyas, Fitria Dwi; Ansori, Isa; Kurnianto, Bagas; Wahyuni, Nur Indah; Xinzhe, Zhao; Nurmanto, Tirza Naya (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2025)
Problem-Solving Skills as an Essential Competency for Elementary School Students is a critical area that can be enhanced through Project-based Scratch Programming technology. This study aims to evaluate the effectiveness of Scratch Programming, applied through projects, on the problem-solving skills of students at SD Negeri Jatisari in Semarang City. The research employed a Quasi-Experimental design using a Pretest-Posttest Non-Equivalent Control Group approach. Participants in the control and experimental groups were not randomly selected, with each group consisting of 27 students. Data analysis techniques included the Independent Sample T-Test and N-Gain Test. Results from the Independent Sample T-Test indicated a significance value of 0.009 (Sig.<0.05), while the N-Gain score for the Experimental Group was 0.40, categorized as Medium. These results demonstrate that the Experimental Group saw a notable improvement in problem-solving skills, particularly in their ability to re-evaluate the outcomes of their problem-solving efforts.